Socio-sanitary Aspects and Microbiological Quality of Drinking Water in the Prefecture of Golfe (Togo) - Djeri, Bouraïma; Kogno, Essozimna; Bilakema, Komlan; Kangni-Dossou, Messanh; Soncy, Kouassi; Taale, Essodolom; Ameyapoh, Yaovi (European Scientific Journal, ESJ, 2019)
Water is essential for life, but its quality is confronted with several problems, including insufficient hygiene and sanitation, which necessitate a contribution to improving the hygienic quality of drinking water. Adescriptive study of 129 randomly selected households was carried out in order to get an idea of the health risks associated with drinking water. Water samples (75) were analyzed using the standardized routine methods described by the European Union. These analyzes related to the following germs: total aerobic flora, total coliforms, thermo tolerant coliforms, Escherichia coli, anaerobic sulfite-reducing bacteria and fecal streptococci. The results showed that 43.41% of households surveyed do not have a source of water at home. Water sources include wells, boreholes, and rainwater. Drinking water storage containers are not covered in 38.89% of the cases. Of the 60 households that have a water source and a latrine at the same time, 27 households or 45% have latrines within 15 meters of the water source. The microbiological analyzes showed that the drinking water samples analyzed are contaminated to varying degrees by the germs retained by the European Union criteria. Total germs and coliforms resulted in high levels of non-compliance. The waters of the storage containers were the most contaminated. Appropriate measures shall be taken for the monitoring and disinfection of these waters before their use.